Benefits, challenges and success factors of water safety plan implementation: A review - Alazaiza, M. Y. D.; Albahnasawi, A.; Al Maskari, T.; Nassani, D. E. (Global Network Environmental Science & Technology, 2022)
Drinking water supply is a preeminent to public health, environmental protection, quality of life, economic activity, and sustainable development. Many disasters are being recorded due to poor water quality every day. In this case, it is essential to assure safe water demand through continuous enhancement and improvement of all practices and processes related to the water supply. The Water Safety Plan (WSP) concept has become a globally recognized and accepted approach to drinking water supply management and operation. This study aims at reviewing the WSP as a risk management approach and the implementation status around the world. In addition, the four success factors of WSP implementation are discussed. The benefits, difficulties, as well as recommendation from recent studies that implemented WSP is presented. The benefits include Improved operational efficiency, improved water quality, reduced consumers, reduced production cost and reduced potential hazardous incidents. However, the main difficulties for effective WSP implementation were lack of staff training, insufficient time and fund were the main challenges. According to a literature scan, the water utilities in Arab gulf region countries do not implement WSP, thus, the author encourages water utilities in these countries to conduct WSP to improve water quality management.
Keywords: Water safety plan; water consumption; risk management; public health